Silent progression in disease activity–free relapsing multiple sclerosis. Issue 5 (30th March 2019) - ,; Cree, Bruce A. C.; Hollenbach, Jill A.; Bove, Riley; Kirkish, Gina; Sacco, Simone; Caverzasi, Eduardo; Bischof, Antje; Gundel, Tristan; Zhu, Alyssa H.; Papinutto, Nico; Stern, William A.; et al.
Abstract : Objective: Rates of worsening and evolution to secondary progressive multiple sclerosis (MS) may be substantially lower in actively treated patients compared to natural history studies from the pretreatment era. Nonetheless, in our recently reported prospective cohort, more than half of patients with relapsing MS accumulated significant new disability by the 10th year of follow‐up. Notably, "no evidence of disease activity" at 2 years did not predict long‐term stability. Here, we determined to what extent clinical relapses and radiographic evidence of disease activity contribute to long‐term disability accumulation. Methods: Disability progression was defined as an increase in Expanded Disability Status Scale (EDSS) of 1.5, 1.0, or 0.5 (or greater) from baseline EDSS = 0, 1.0–5.0, and 5.5 or higher, respectively, assessed from baseline to year 5 (±1 year) and sustained to year 10 (±1 year). Longitudinal analysis of relative brain volume loss used a linear mixed model with sex, age, disease duration, and HLA‐DRB1*15:01 as covariates. Results: Relapses were associated with a transient increase in disability over 1‐year intervals ( p  = 0.012) but not with confirmed disability progression ( p  = 0.551). Relative brain volume declined at a greater rate among individuals with disability progression compared to those who remained stable ( p  < 0.05). Interpretation: Long‐term worsening is common in relapsing MS patients, is largely independent of relapse activity, and is associated with accelerated brain atrophy. We propose the term silent progression to describe the insidious disability that accrues in many patients who satisfy traditional criteria for relapsing–remitting MS. Ann Neurol 2019;85:653–666